The complex of miRNA2861 and cell-penetrating, dimeric α-helical peptide accelerates the osteogenesis of mesenchymal stem cells - So Hee Nam; Yan Lee; Chi-Heon Kim; Dong Eun Kim; Hee-Jin Yang; Sung Bae Park (Biomaterials Research, 2022)
Abstract Background The restoration of the functional ability of mesenchymal stem cells (MSCs) using epigenetic modification is very promising for patients with weak osteogenesis ability. This study focused on the acceleration of osteogenesis from MSCs using microRNA (miRNA)2861 and a cell-penetrating peptide (CPP), LK. Methods We performed MSCs penetration test of complex between the LK peptides and miRNA 2861. Three different experiments were performed to investigate the effects of miRNA 2861 on osteogenic differentiation in MSCs: 1) intensity of alizarin red staining, which reflects the status of mineralization by osteoblasts; 2) gene expression related to osteoblast differentiation; and 3) confirmation of corresponding protein translation for comparison with RNA expression levels. Results We found that cLK effectively delivered miRNA 2861 into the cytoplasm of human MSCs and accelerated osteogenic differentiation from MSCs, as well as mineralization. Conclusion The complex of miRNA 2861 with LK may have a positive effect on the osteogenic differentiation from MSCs and mineralization. Therapies using miRNAs combined with LK may be good candidates for the augmentation of osteogenesis in patients.